2011
DOI: 10.1149/2.034112jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Activity and Stability of M-Fe Catalysts Synthesized by Polymer Complex Method for PEFC Cathode

Abstract: The polymerized complex (PC) method was used to synthesize highly dispersed iron-based catalysts for the oxygen reduction reaction (ORR). The catalysts were prepared with an addition of 1,10-phenanthroline (Phen) and transition metals (M), such as Ta, Ti, and W, in an attempt to enhance the ORR activity and durability of the catalysts. The composition and properties of the catalysts were characterized by thermogravimetric analysis, X-ray diffraction, and X-ray photoelectron spectroscopy. The catalyst component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…As an Fe-containing reference electrode catalyst, an Fe-based Ti-containing catalyst was prepared by the PC method, as described in our previous paper . The catalysts were prepared using 1,10-phenanthroline and NH 3 gas as the nitrogen source and formed Fe-based active sites for ORR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an Fe-containing reference electrode catalyst, an Fe-based Ti-containing catalyst was prepared by the PC method, as described in our previous paper . The catalysts were prepared using 1,10-phenanthroline and NH 3 gas as the nitrogen source and formed Fe-based active sites for ORR.…”
Section: Methodsmentioning
confidence: 99%
“…The first example was a catalyst consisting of transition-metal Fe or Co complexes dispersed in macrocyclic structures such as porphyrin, phenanthroline, phthalocyanine, polyacrylonitrile, polypyrrole, or polyaniline. Later, carbon-based materials, even without transition metals, especially when doped with nitrogen, were reported to exhibit excellent ORR activity. Nevertheless, none of these electrocatalysts has reached the catalytic activity of Pt-based electrocatalysts, and stability in an acidic environment remains an unsolved issue. Another approach for developing non-noble-metal cathodes is the use of groups IV and V transition metals, because of their abundance and high stability in acidic media. Ota et al reported that partially oxidized TaC x N y , ZrC x N y , and NbC x N y showed onset potentials for the ORR comparable to those of Pt-based catalysts while remaining highly stable under PEFC cathode conditions. Until recently, because the synthesis of these catalysts required high-temperature treatment, only bulky, low surface area particles were produced with diameters up to 100 nm, resulting in low current densities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, Pt material is both expensive and low abundance, which have been identied to be the major contributors to the challenges of high-cost of PEM fuel cells. 2,4,8 Furthermore, regarding the challenge of insufficient durability, there are two major contributing factors including (1) the cathode Pt catalyst is easily to be dissolved when the electrode is performed in a highly acidic environment and polarized at a positive potential, 9 and (2) Pt catalysts can be easily poisoned by the impurities in the feed system, resulting in performance degradation. 4,10,11 To overcome these challenges, developing alternative ORR electrocatalysts such as non-precious metal catalysts (NPMCs) have been becoming the most active approach in fuel cell catalyst research and development in the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…6 To make PEM fuel cells technically feasible and practical, in the current state of technology, Pt-based catalysts must be used to catalyze the slow ORR due to their high catalytic performances for both the anode and cathode. However, as Pt-based catalysts have insufficient electrochemical durability and come at a high cost, [6][7][8] the major efforts in PEM fuel cell research and development have been put into reducing Pt loading by exploring more active catalysts, and/or replacing Pt metal with other, nonprecious, metals such as Fe, Co and Cu. 9,10 In spite of current progress, very few examples show real promise to be comparable to Pt since the requirements for both good ORR activity and stability are difficult to achieve for normal non-noble catalysts in the strongly acidic conditions of PEM fuel cell operation.…”
Section: Introductionmentioning
confidence: 99%